Unloading Mechanics and Energy Characteristics of Sandstone under Different Intermediate Principal Stress Conditions - Yingjie Zhang; Jiangteng Li; Gang Ma; Shuangfei Liu (Advances in Civil Engineering)
The TRW-3000 true triaxial rock testing machine was used to conduct loading and unloading tests of sandstone under different σ2, and the true triaxial lateral unloading mechanics and energy characteristics of sandstone under different σ2 were studied. The experimental results show the following: (1) compared with the results of the loading test, the peak strength of the sandstone under the unloading σ3 path is reduced, the unloading direction has obvious expansion and deformation, and the amount of expansion increases significantly with the increase of σ2; sudden brittle failure occurs at the end of unloading. E gradually decreases with the increase of H, and it performs well to use the cubic polynomial to fit the curve of E-H. (2) The Mogi–Coulomb strength criterion can accurately describe the true triaxial strength characteristics of sandstone under loading and unloading conditions. Compared with the results of the loading test, the values of c and φ obtained based on this criterion under the unloading σ3 path are reduced. (3) Under the condition of unloading σ3, U,Ue, and Ud, when the specimen is broken, are all linearly positively correlated with σ2. Ud increases nonlinearly with the increase of H, and as σ2 increases, the slope of the Ud-H curve becomes larger, and the specimen consumes more energy under the same unloading amount. Most of the energy absorbed by the specimen under the unloading σ3 path is converted into Ue, but as σ2 increases, Ud /U increases, and the energy consumed when the specimen is broken is greater.